2003
DOI: 10.1002/bem.10120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ELF magnetic field on membrane protein structure of living HeLa cells studied by Fourier transform infrared spectroscopy

Abstract: The effects of exposure to a 50 Hz magnetic field (maximum of 41.7 to 43.6 mT) on the membrane protein structures of living HeLa cells were studied using attenuated total reflection infrared spectroscopy. One min of such exposure shifted peak absorbance of the amide I band to a smaller wave number, reduced peak absorbance of the amide II band, and increased absorbance at around 1600 cm(-1). These results suggest that exposure to the ELF magnetic field has reversible effects on the N-H inplane bending and C-N s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Santoro et al [1997] showed that extremely low frequency (ELF) MFs influence physiological processes in different organisms, such as plasma membrane structure modification and initiation of signal cascade pathways interference. Cell membrane morphology modification by ELF was again reaffirmed by Ikehara et al [2003], who found that exposure to the ELF MF has reversible effects on N─H inplane bending and C─N stretching vibrations of peptide linkages, and changes the secondary structures of a-helix and b-sheet in cell membrane proteins.…”
Section: Introductionmentioning
confidence: 78%
“…Santoro et al [1997] showed that extremely low frequency (ELF) MFs influence physiological processes in different organisms, such as plasma membrane structure modification and initiation of signal cascade pathways interference. Cell membrane morphology modification by ELF was again reaffirmed by Ikehara et al [2003], who found that exposure to the ELF MF has reversible effects on N─H inplane bending and C─N stretching vibrations of peptide linkages, and changes the secondary structures of a-helix and b-sheet in cell membrane proteins.…”
Section: Introductionmentioning
confidence: 78%
“…Previous studies show that exposure to a static magnetic field resulted in an increased Ca +2 level in numerous cells, including macrophages [50], astrocytoma cells [51], [52], and chromaffine cells [53]. This increase of [Ca +2 ]i may be mediated by the change of the structure and dynamic properties of lipid membrane [54], [55], membrane potential and cell surface charge [56], protein structure [57], [58], and intramembrane proteins distribution [59]. [Ca +2 ]i is mainly increased by either stimulation of Ca +2 influx mediated by the Ca +2 channel of the cell membrane or Ca +2 released from intracellular Ca +2 stored when a static magnetic field is applied [60], [61].…”
Section: Discussionmentioning
confidence: 98%
“…This molecular rotation within the membrane matrix influences the imbedded ion channels, most likely by producing some degree of deformity of their intramembranous segment, i.e., the part of the structure which is responsible for activation [22,23]. ELF-PMF exposure also influences the lipid components of the cellular membrane, and the N-H in-plane bending and C-N stretching vibrations of peptide linkages, modifying the secondary structures of α-helix and β-sheet contents and producing unfolding process in cell membrane proteins of Hela (41.7-43.6 mT, 50 Hz, ELF-PMF, for up to 1 min) and differentiated SH-SY5Y cells (0.81-1.41, 50 Hz, ELF-PMF, for up to 4 h) [17,24]. Thus, MF affects membrane proteins either directly, or indirectly through the neighbouring phospholipids [17,22,23].…”
Section: Alteration Of Building Moleculesmentioning
confidence: 99%